2018
DOI: 10.1080/15476286.2018.1556149
|View full text |Cite
|
Sign up to set email alerts
|

The human RNA helicase DHX37 is required for release of the U3 snoRNP from pre-ribosomal particles

Abstract: Ribosome synthesis is an essential cellular process, and perturbation of human ribosome production is linked to cancer and genetic diseases termed ribosomopathies. During their assembly, pre-ribosomal particles undergo numerous structural rearrangements, which establish the architecture present in mature complexes and serve as key checkpoints, ensuring the fidelity of ribosome biogenesis. RNA helicases are essential mediators of such remodelling events and here, we demonstrate that the DEAH-box RNA helicase DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 60 publications
4
50
0
1
Order By: Relevance
“…9A,B; Supplemental Table S1), suggesting that UTP14A functions as an activator of DHX37 in part by increasing its RNA-dependent ATPase activity. This result stands in contrast to a previous observation that yeast Utp14 increases the RNA unwinding activity of Dhr1 in vitro without affecting ATPase activity (Zhu et al 2016) but is in good agreement with a recent study of human DHX37 (Choudhury et al 2018). Although DHX37 and Dhr1 have similar biological functions, it is possible that they use divergent molecular mechanisms.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…9A,B; Supplemental Table S1), suggesting that UTP14A functions as an activator of DHX37 in part by increasing its RNA-dependent ATPase activity. This result stands in contrast to a previous observation that yeast Utp14 increases the RNA unwinding activity of Dhr1 in vitro without affecting ATPase activity (Zhu et al 2016) but is in good agreement with a recent study of human DHX37 (Choudhury et al 2018). Although DHX37 and Dhr1 have similar biological functions, it is possible that they use divergent molecular mechanisms.…”
Section: Resultssupporting
confidence: 83%
“…Recent studies have suggested that UTP14A functions as a ribosome biogenesis factor in part by recruiting DHX37 to the maturing preribosomal particle (Choudhury et al 2018). Our biochemical experiments reveal that a conserved motif in UTP14A, distinct from the canonical DEAH-interacting motif found in G-patch proteins, is necessary and sufficient for interaction with DHX37.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Variants of the DEAH-box helicase 37 (DHX37) gene have recently been identified as an important cause of 46,XY GD, especially for embryonic testicular regression syndrome (ETRS). DHX37 is an RNA-helicase which has a role of DHX37 in ribosome biogenesis [125] and is expressed in the somatic cell lineage of the mouse and human (7-12 weeks of gestation) gonad early during testis determination and development [126]. Co-expression with Sox9 in a proportion of cells indicates the presence of DHX37 in Sertoli cells [126], whilst it is also expressed in Leydig cell cytoplasm and in germ cells at different stages of maturation (27 and 33 weeks of gestation) and, in adult human testes, the protein is mainly localized in spermatogonia [126,127].…”
Section: Dhx37: a Novel Participant Of Gonadal Development And Maintementioning
confidence: 99%
“…Although the roles of some RNA helicases are common to yeast and humans (e.g. yeast Dhr1 and human DHX37 both mediate release of the U3 snoRNA; Martin et al , ; Sardana et al , ; Choudhury et al , ), additional pre‐ribosomal functions have been described for several human RNA helicases. Examples include the requirement for DDX51 for release of the metazoan‐specific snoRNA U8 from pre‐LSU complexes (Srivastava et al , ), as well as the roles of DDX21 in coupling pre‐rRNA transcription and processing, and facilitating the access of late‐acting small nucleolar RNP (snoRNPs) to pre‐40S complexes (Calo et al , ; Sloan et al , ).…”
Section: Ribosome Production: Going Beyond the Yeast Model Systemmentioning
confidence: 99%